1997
DOI: 10.1073/pnas.94.22.11808
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for a second sialic acid binding site in avian influenza virus neuraminidases

Abstract: The x-ray structure of a complex of sialic acid (Neu5Ac) with neuraminidase N9 subtype from A͞tern͞ Australia͞G70C͞75 inf luenza virus at 4°C has revealed the location of a second Neu5Ac binding site on the surface of the enzyme. At 18°C, only the enzyme active site contains bound Neu5Ac. Neu5Ac binds in the second site in the chair conformation in a similar way to which it binds to hemagglutinin. The residues that interact with Neu5Ac at this second site are mostly conserved in avian strains, but not in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
151
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(163 citation statements)
references
References 39 publications
6
151
1
4
Order By: Relevance
“…An HB site was created in the non-hemagglutinating N2 NA by substituting amino acids from two loops of N9 NA into N2 NA 58 . In N9 NA, an X-ray crystal structure (Figure 3) showed a sialic acid molecule bound in the predicted HB site, contacting amino acids Ser367, Ser370, Ser372, Asn400, Trp403 and Lys432 (N2 numbering) 59 . This site bears no resemblance to either the NA active site or the HA sialic acid binding site, and indeed the specificity of binding is unlike that of HA, in that the bound sialic acid is not released by N9 or N2 NA activity but only by bacterial sialidases of very broad specificity 60 .…”
Section: Some Nas Have a Second Sialic Acid Binding Sitementioning
confidence: 99%
See 2 more Smart Citations
“…An HB site was created in the non-hemagglutinating N2 NA by substituting amino acids from two loops of N9 NA into N2 NA 58 . In N9 NA, an X-ray crystal structure (Figure 3) showed a sialic acid molecule bound in the predicted HB site, contacting amino acids Ser367, Ser370, Ser372, Asn400, Trp403 and Lys432 (N2 numbering) 59 . This site bears no resemblance to either the NA active site or the HA sialic acid binding site, and indeed the specificity of binding is unlike that of HA, in that the bound sialic acid is not released by N9 or N2 NA activity but only by bacterial sialidases of very broad specificity 60 .…”
Section: Some Nas Have a Second Sialic Acid Binding Sitementioning
confidence: 99%
“…HB activity was also found in the N1 NA of fowl plague virus 61 . Comparisons of sequences in the area of the second binding site suggested that avian viruses have the HB activity while human viruses do not 59,61,62 , but so far a specific function of the HB activity in bird viruses has not been established.…”
Section: Some Nas Have a Second Sialic Acid Binding Sitementioning
confidence: 99%
See 1 more Smart Citation
“…We ran these 3 programs and recorded score values for the top ranked poses whose RMSD's from crystal structures are under 2.0 Å. The experimental IC50 values for the featured inhibitors are taken from literature [23][24][25][26][27][28] and converted to binding affinities. Table 1 shows calculated binding affinities along with the experimental values.…”
Section: Resultsmentioning
confidence: 99%
“…II, III). In addition to having few anti-NA antibody determinants as proposed for strain 575 [22,24], further examinations [10,11,13,31,32] may find that certain NDV strains may have an HA and perhaps a second NA binding site; such is the case with the frequently isolated [23] avian influenza subtype 9 [50].…”
Section: Discussionmentioning
confidence: 99%